Parallel detection of multiple zoonotic parasites using a real-time fluorogenic loop-mediated isothermal amplification-based quadruple-sample microfluidic chip - Chen, Yu-Xin; Lou, Yi-Rong; Duan, Li-Jun; Zhou, Qian-Jin; Xu, Zhong-Jie; Chen, Fang-Jie; Chen, Hong-Xian; Xu, Gui-Zong; Du, Ai-Fang; Chen, Jiong (Frontiers in Microbiology, 2023)
Zoonotic parasites pose significant health risks globally. In the present study, we combined a microfluidic chip with loop-mediated isothermal amplification (on-chip LAMP) to detect five zoonotic parasites: Toxoplasma gondii, Cryptosporidium parvum, Cryptosporidium hominis, Clonorchis sinensis, and Taenia solium. This method enabled the simultaneous parallel analysis of five genetic markers from a maximum of four samples per chip. The on-chip LAMP assay was conducted in a highly automated format via the addition (by pipetting) of each sample in a single operation. The reaction was performed in volumes as low as 5 μL at a temperature of 65°C for 60 min, achieving limits of detection ranging from 10−2 to 10−3 pg./μL of recombinant plasmid DNA. All the time-to-positive values were less than 40 min, and almost all the coefficients of variation were less than 10%, even when using limit of detection concentrations for multiple pathogens, indicating robust reproducibility among replicates. The clinical sensitivity and specificity for detecting 135 field samples were 98.08 and 97.59%, respectively, compared with traditional biological methods, indicating good applicability in the detection of field samples. This on-chip LAMP assay allows for low reagent consumption, ease of operation, and multiple analyses of samples and genetic targets, and is applicable for on-site detection and the routine monitoring of multiple zoonotic parasites.